Aladin-et la lampe - Beaumont, P. De; Lulla, Sunil; Vishal & Shekhar (Musical group); Eros International (Firm) (Mumbai : Eros International Media, 2009)
Based in the municipality of Khwaish, abused by his classmates, Aladin Chatterjee, who was orphaned when his parents, Arun and Riya, died in an accident in Siachen Valley, lived with his paternal grandfather until the later's passing. Now alone, grown up, studying in Khwaish University, and still being abused by fellow-college mates, he finds himself smitten by the lovely US Exchange Student, Jasmine. Unable to express his feelings for her, he rubs a lamp that was gifted to him on his birthday, which summons a genie named Genius. He gets 3 wishes, but wastes 2 of them, but on the 3rd one he insists that Genius assist him to win Jasmine's heart without any magical tricks. Hilarious chaos results when everything seems to fail; while an immortal and deadly entity, Ringmaster, and his hordes, prepares to confront Genius and Aladin so that he can acquire even more magical powers with the help of the lamp on the day of the sighting of a rare comet; and the truth behind the death of Aladin's parents.
Disc 1. Movie (ca. 130 min.) -- Disc 2. Special features (ca. 69 min.)
Copyright notice on disc: Eros International.
Discs 1-2 are together in one container.
Originally released theatrically in 2009.
Summary taken from IMDb.com.
Music, Vishal-Shekhar ; lyrics, Vishal Dadlani, Anvita Dutt Guptan ; choreographer, Bosco Ceaser, Shamak Davar ; editor, Suresh Pai ; art direction, Saby Cyril.
Amitabh Bachchan, Ritesh Deshmukh, Bomab Irani, Sanjay Dutt, Jacqueline Fernandez, Shubhankar Atre.
Keywords: Aladdin -- (Legendary character) -- Drama; Genius (Companion spirit) -- Drama